OP0232 Monitoring anti-interleukin 6 receptor antibody treatment in rheumatoid arthritis and prediction progressive structural damage of the wrist joints by ultrasonography. (23rd January 2014) - Volkov, A.; Osipyants, R.; Panasyuk, E.; Smirnov, A.; Lukina, G.; Gluchova, S.; Aleksandrova, E.; Karateev, D.; Nasonov, E.
Abstract : Objectives: To evaluate the responsiveness of grey scale (GS) or power Doppler (PD) ultrasonography (US) compared with conventional measures of disease activity and to predict structural damage in patients (pts) with rheumatoid arthritis (RA) during 6 months of treatment with anti-IL 6 receptor antibody - tocilizumab (TCZ). Methods: Pts with RA (N=46, median age 48.5 (range 39-55) years, disease duration 60 months, 83% "+" for RF and anti-CCP) were included at the start of treatment with TCZ. All pts were divided into two groups: 1st (n=11) – pts with disease duration <2years, 2nd (n=36) – more two years. US ("Voluson-i" (GE, USA), 4-13MHz probe) was performed at baseline (n=46) and after 6 months (n=42), and included bilateral the wrist joints. Each joint was scored according to the OMERACT definitions of pathology [1]. Clinical (28 tender/swollen joints count (JC) and DAS28) and laboratory data (ESR, CRP) were obtained at each time of assessment. Standardized Response Means (SRM) were calculated for the changes of the variables over time (SRM = mean change/SD change). Accepted thresholds for effect size were applied to classify responsiveness as trivial, low, moderate or large. Hand, feet X-ray were performed at the entry and at one year. Radiographic progression was defined when the change of the van der Heijde-modified total Sharp score (Δ TSS) more than 0.5 units per year. Results: SRM for change scores for US findings, clinical and laboratory data shown in the table. High responsiveness (>0.80) for GS, PD scores were observed only pts with disease duration <2 years as well as for swollen JC. Δ TSS (between M0 and M12) were significantly positively correlated with the PD score of the wrists at 6 months (r=0.669, p=0.008), but were not found correlations with the GS score and other markers of inflammatory. Conclusions: US in GS and PD is a helpful tool in reflecting therapy response to TCZ (especially at pts with disease duration <2 years). The PDUS score of the wrists at 6 months may be a good predictor of long-term radiographic damage. References: Wakefield RJ, Balint PV, Szkudlarek M, Filippucci E, Backhaus M, D'Agostino M et al. Proceedings from the OMERACT Special Interest Group for Musculoskeletal Ultrasound including definitions for ultrasonographic pathology. J Rheumatol 2005; 32:2485-7. Disclosure of Interest: None Declared